Screening the ability of several microbial isolates for production of some industrial enzymes - Ibtisam M. Ahmadi, Mabrouka I. Abuzeid, Massoudah O. Khalifa, Naeema A. Matuoog, Asma I. Abdasalam (Journal of Pure & Applied Sciences, 2020)
microbes release more stable enzymes which can be obtained at the lowest coast. Species of fungi and bacteria were isolated from different sources including Aspergillus niger, Aspergillus flavus, Penicillium chrysogenum, Fusarium solani ;Pseudomonas aeruginosa, Bacillus mycoides and Bacillus cereus as well as two isolates of Rhizobia, BUS26 and RMI4 in addition to the Ensifer meliloti as a reference strain of rhizobia. These microbial species were used to determine their ability to produce some industrial enzymes after culturing them on Czapek dox agar by replacing the carbon source with pectin, chitin or cellulose. Then the average diameter of the colony was measured and the percentage of the enzymes production was calculated. The results showed that all the fungus utilized in this study produced the enzymes in different proportions. A. niger isolated from air and soil was able to grow and use orange peel as a single source of carbon to produce pectinase with the highest percentage of 80.77% and 71.72% respectively. As well as the highest yield of cellulase was produced by A. niger with a rate of 81.15%, while the rest of fungi differed in their ability to produce the enzymes between the medium and low amount. F. solani had the lowest ability to produce pectinase and chitinase by rates of 19.21% and 17.03% respectively. The ability of bacterial isolates to produce enzymes was also varied as B.mycoides and BUS26 gave the highest productivity of cellulase by 74.74% and 68.89% respectively. The productivity of pectinase was close as BUS26 isolate showed productivity rate of 50% following by P.aeruginosa with a ratio of 47.83% while B.cereus had a pectinase production with a rate of 34.66%.